2000
DOI: 10.1366/0003702001949203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Self-Assembling of Butan-1-ol, Butan-2-ol, and 2-Methylpropan-2-ol in Carbon Tetrachloride Solutions as Observed by Near-Infrared Spectroscopic Measurements

Abstract: The self-associations of butan-1-ol, butan-2-ol, and 2-methylpropan-2-ol ( tert-butanol) in the pure liquid state and in carbon tetrachloride solutions have been studied mainly through near-infrared spectroscopic observation at various temperatures. A new analysis assuming a successive association process for the alcohol molecules was applied to the sharp band around 1410 nm (the first-overtone band of the OH stretching vibration mode attributed to free OH monomer and partly to OH polymer); it became clear tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…A number of QM studies on NIR spectra of basic molecules have been reported over the last few years (Beć et al, 2016a, 2018a; Grabska et al, 2017a,b). Vibrational studies of these systems are relatively important for our understanding of the general spectra-structure correlations (Czarnecki et al, 2000; Wojtków and Czarnecki, 2006; Michniewicz et al, 2007, 2008; Haufa and Czarnecki, 2010) and the role of conformational isomerism (Czarnecki et al, 2006; Wojtków and Czarnecki, 2006), structure and dynamics of hydrogen-bonding, self-association mechanisms and intermolecular interactions (Czarnecki and Ozaki, 1999; Czarnecki et al, 2000, 2010; Czarnecki, 2003; Czarnecki and Wojtków, 2004; Michniewicz et al, 2007; Haufa and Czarnecki, 2010), in particular the interactions with solvent molecules (e.g., water, nonpolar solvents) (Gonjo et al, 2011; Tomza and Czarnecki, 2015), or chiral discrimination (Czarnecki, 2003); the temperature influence on the above effects was often also examined (Czarnecki and Ozaki, 1999; Iwahashi et al, 2000; Šašić et al, 2002; Wojtków and Czarnecki, 2005, 2006, 2007; Grabska et al, 2017a). In the above contexts, alcohol molecules have remained among those investigated most frequently in physicochemical NIRS; often, the lack of QM spectra simulations hindered full comprehension therein.…”
Section: Theoretical Near-infrared Spectroscopy–an Overview Of the Emmentioning
confidence: 99%
“…A number of QM studies on NIR spectra of basic molecules have been reported over the last few years (Beć et al, 2016a, 2018a; Grabska et al, 2017a,b). Vibrational studies of these systems are relatively important for our understanding of the general spectra-structure correlations (Czarnecki et al, 2000; Wojtków and Czarnecki, 2006; Michniewicz et al, 2007, 2008; Haufa and Czarnecki, 2010) and the role of conformational isomerism (Czarnecki et al, 2006; Wojtków and Czarnecki, 2006), structure and dynamics of hydrogen-bonding, self-association mechanisms and intermolecular interactions (Czarnecki and Ozaki, 1999; Czarnecki et al, 2000, 2010; Czarnecki, 2003; Czarnecki and Wojtków, 2004; Michniewicz et al, 2007; Haufa and Czarnecki, 2010), in particular the interactions with solvent molecules (e.g., water, nonpolar solvents) (Gonjo et al, 2011; Tomza and Czarnecki, 2015), or chiral discrimination (Czarnecki, 2003); the temperature influence on the above effects was often also examined (Czarnecki and Ozaki, 1999; Iwahashi et al, 2000; Šašić et al, 2002; Wojtków and Czarnecki, 2005, 2006, 2007; Grabska et al, 2017a). In the above contexts, alcohol molecules have remained among those investigated most frequently in physicochemical NIRS; often, the lack of QM spectra simulations hindered full comprehension therein.…”
Section: Theoretical Near-infrared Spectroscopy–an Overview Of the Emmentioning
confidence: 99%
“…7 Therefore, many reports on NIR spectroscopy can be found in the research field of hydrogen bonding, especially for simple alcohol molecules. 816 We also used NIR spectroscopy to examine the molecular interaction between methanol and nonpolar and polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,10,11 These nonpolar matrices are used for assigning the IR and NIR bands due to the O–H stretching modes in several types of hydrogen-bonding states 211 and for estimating the proportions of the hydrogen-bonded species in different nonpolar solvents. 1113…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we have examined in detail the hydrogen bonds in ME-CCl 4 , ME-DMSO, and ME-acetone systems with excess infrared spectroscopy. Carbon tetrachloride is a common nonpolar solvent, [26][27][28] and it is used here as an inert solvent to obtain information on association and dissociation of ME molecules themselves. DMSO and acetone are typical proton acceptors (the b H 2 values are 0.78 for RSOMe and 0.49 for RCOMe), 19,29 both forming hydrogen bonds with OH and SH groups.…”
Section: Introductionmentioning
confidence: 99%